2013
DOI: 10.1002/ange.201209317
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Intramolecular ipso‐Friedel–Crafts Alkylation of Phenols and Indoles: Rearomatization‐Assisted Oxidative Addition

Abstract: Inspiroierend: Eine neuartige Synthese von Spirocyclen basierend auf einer Palladium‐katalysierten intramolekularen ipso‐Friedel‐Crafts‐Alkylierung von Phenolen (siehe Schema; dba=Dibenzylidenaceton) und Indolen wird beschrieben. Mechanistische Studien belegen, dass die Reaktion über eine präzedenzlose Rearomatisierungs‐unterstützte oxidative Addition verläuft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, this catalytic system was also effective for difluoromethylenative dearomatization of indoles 3c,4. When indole derivative 4 was treated under the optimized reaction conditions, aza‐spirocyclic adduct 5 was obtained in good yield [Equation (2)].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, this catalytic system was also effective for difluoromethylenative dearomatization of indoles 3c,4. When indole derivative 4 was treated under the optimized reaction conditions, aza‐spirocyclic adduct 5 was obtained in good yield [Equation (2)].…”
Section: Resultsmentioning
confidence: 96%
“…In the same year, You et al developed a procedure for iridium‐catalyzed asymmetric allylic dearomatization of phenols with excellent yields and enantioselectivities (Scheme , b) 3f. More recently, Hamada's group discovered a palladium‐catalyzed approach to ipso ‐Friedel–Crafts alkylation of phenols (Scheme , c); this kind of method can also be applied to dearomatization of indoles 3c…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a novel method for synthesizing spiro[4.5]cyclohexadienones based on a Pd‐catalyzed intramolecular ipso ‐Friedel–Crafts allylic alkylation of phenols 6. The present reaction mode could be further extended to the synthesis of spiro[5.5]cyclohexadienones using η 3 ‐propargyl‐palladium(II) complexes as electrophiles7 (Scheme ). Based on this background, we hypothesized that an analogous spirocyclization should proceed through an intramolecular ipso ‐Friedel–Crafts‐type addition of phenols to alkynes activated by electrophilic gold catalysts, affording spirocyclohexadienones with an exo ‐cyclic olefin unit.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that h 3 -propargylpalladium(II) intermediates coulds erve as effective electrophilicp artnersi n ap alladium-catalyzedi ntramolecular ipso-Friedel-Crafts alkylation of para-substituted phenols. [8,9] We hypothesized that this reactionm ode could be applicable to the synthesis of 3,4fused tricyclic indoles (Scheme 1b). If meta-substituted aniline derivatives are utilized as substrates, aF riedel-Crafts-type CÀH coupling with h 3 -propargylpalladium(II) intermediates would occur at the ortho-position to the aniline to give p-allylpalladium(II) species.T he following CÀNb ond formation would afford 3,4-fusedt ricyclic 3-alkylidene indolines.E xtensive efforts based on this workingh ypothesis illustrated the overwhelming advantage of platinum catalysts for this reaction.…”
mentioning
confidence: 99%
“…[11] Asimilar rapid palladacycle formation/reductive elimination process was also observed in our previousi ntramolecular ipso-Friedel-Crafts alkylation of phenols, reasonablys upporting this mechanistic consideration. [8] Sequential 6-endo or 5-exo cyclization of 5a proceeded under the reaction conditions, producing compound 2a or 3a,r espectively. [12] To make the desired pathway operative, selective promotion of the Friedel-Craft-type process from the h 3 -propargylpalladium(II) intermediate III is required.…”
mentioning
confidence: 99%